A dramaturgical perspective of online university student behaviours in a second year psychology class - Gilmore, Dawn Marie (Online Learning, 2020)
This study applies dramaturgical sociology, specifically Goffman’s approach to region behaviour, to explore where students spend their time doing class related tasks in spaces other than the LMS. The context for this research is a case study of a second year psychology class at an Australian university. Data was collected about students’ front stage setting (the LMS) and backstage setting (students’ experiences on Facebook). Over a 12-week semester 126 students were observed in the LMS. During the semester, 21 students completed fortnightly questionnaires about where they spent their time and with whom. At the end of the semester, 14 students participated in online interviews. The findings that emerged from the data illustrated how the characteristics of the audience in each setting, as well as the timing of communication and duration of each setting, may have impacted a student’s social learning experience. This knowledge can help online teachers to understand the characteristics of a setting that might determine where students prefer to situate their learning experience. While this paper uses a dramaturgical perspective of online university students in a second year psychology class, the students’ experiences can generally be used to understand how LMS’s, social networking tools, and collaborative technologies support and impede social learning experiences in higher education.